The Development of a Model for Promoting Family Resilience with Guardians of Children and Youths Diagnosed with Acute Lymphoblastic Leukemia - Suparit, Surangkana; Junprasert, Thasuk; Sakunpong, Nanchatsan (Journal of Behavioral Science for Development, 2024)
The objective of this study is to develop a model for promoting family resilience with guardians of children and youths who diagnosed with acute lymphoblastic leukemia. The study based on technical action research, collecting data by interviewing and observation, analyzing data by clustering, classify, encode and draw conclusions from the findings. The research participants, include 14 guardians who play a close role in caring for children and youths with acute lymphoblastic leukemia, and 3 experts. The result of the model for promoting family resilience identified four processes: 1) Researchers and experts gain an understanding of the process and factors related to family resilience, including the need for family development from guardians. 2) Researchers provide social support and create awareness of social support sources for guardians. 3) Researchers reinforce positive feelings and thoughts in both themselves and the guardians' surrounding people. 4) Guardians share their family resilience experiences with new guardians, resulting in changes in the three-dimensional model for promoting family resilience, including knowledge and understanding, emotional, and behavioral family resilience. The results of this study on the model for promoting family resilience with guardians of children and youths diagnosed with acute lymphoblastic leukemia can be further applied and utilized by guardians in future crisis situations. Additionally, interdisciplinary teams or public health organizations can apply this model to enhance services provided to families of patients in the future.